A Novel Approach to Selecting Rational Supports for Underground Mining Workings - Almenov, Talgat; Zhanakova, Raissa; Sarybayev, Madiyar; Shabaz, Din-Mukhammed (Civil Engineering Journal, 2025)
The goal of this study is to examine the stress-strain state and stability of rock massifs to select a rational type of support for underground workings in challenging mining and geological conditions. The primary aims include increasing the speed of mine workings, reducing capital expenditure, and enhancing safety. Established and novel theoretical methods for mining, geomechanics, and rock massif management were employed. These methods involve analyzing factors affecting the mine working speed, studying the physical and mechanical properties of rocks, developing stratigraphic profiles, and assessing the stress-strain state and stability using Bieniawski’s Rock Mass Rating (RMR), Barton’s Q-rating, and construction norms and rules. Numerical modeling with the Rocscience RS2/RS3 software was utilized to identify failure-prone areas and determine rational support types and parameters. This study provides comprehensive insights into the stress-strain state of the massif, identifying high-risk zones, and recommending suitable support types. The findings contribute to accelerating the progress of underground work, enhancing safety, and reducing construction costs. The developed support systems for challenging mining and geological conditions were designed to increase the speed, safety, and profitability of underground workings. Additionally, this research emphasizes the significance of selecting appropriate support systems to ensure the longevity and stability of underground structures, thereby optimizing operational efficiency and cost-effectiveness. Doi: 10.28991/CEJ-2025-011-03-022 Full Text: PDF